Residents' attitudes toward impacts of tourism development: a case of Kundasang, Sabah / Khairul Azmi Abdul Rahman - Abdul Rahman, Khairul Azmi (2012)
It is crucial to conduct a study on the residents' attitude toward impacts of tourism development in order to maintain the sustainability of tourism development. To understand the residents' attitude, Doxey's Irridex Model is used as a framework. However, several studies have found that this model is not applicable in certain communities. To obtain reliable results, standardized instrument to measured attitude of the residents was developed and used and Fishbein's attitude model used to design questions. Moreover, to obtain appropriate sample size, the most practical sampling technique was used that is Probability proportional to size (PPS). The data is analyzed using Statistical Package for Social Science (SPSS). The findings revealed that, residents favoured and perceived impact that benefit them as positive impact of tourism development, while did not favoured the impact that did not bring any benefits as negative impacts of tourism. The finding also revealed that Doxey Irridex Model is not applicable in the area of study and not support the model. Finally, policy maker and tourism planner should concern the findings of this paper to gain favourable results in maintaining sustainable tourism development particularly in Kundasang, Sabah.